Allergy, inflammation, hepatopathy and coagulation biomarkers in dogs with suspected anaphylaxis due to insect envenomation - Kate Turner; Corrin Boyd; Gabriele Rossi; Claire R. Sharp; Claire R. Sharp; Melissa A. Claus; Abbie Francis; Abbie Francis; Lisa Smart; Lisa Smart (Frontiers in Veterinary Science, 2022)
ObjectivesTo compare concentrations of biomarkers of; allergy [mast cell tryptase (MCT) and histamine], inflammation [interleukin (IL)-6,-10, and−18, CXCL8, CCL2, keratinocyte chemoattractant (KC), C-reactive protein (CRP)], endothelial glycocalyx shedding (hyaluronan), coagulation [prothrombin time, activated partial thromboplastin time, fibrinogen concentration, and von Willebrand Factor antigen, protein C (PC) and antithrombin (AT) activity], and hepatopathy [alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), and total bilirubin] between dogs with anaphylaxis after suspected insect exposure, dogs with critical illness, and healthy dogs.DesignThis was a single center prospective clinical observational comparative biomarker study that included 25 dogs with anaphylaxis (evidence of insect exposure, acute dermatological signs, and other organ involvement), 30 dogs with other critical illness, and 20 healthy dogs. Differences across groups in biomarker concentrations were tested using one-way ANOVA or Kruskal-Wallis test, with significant P values (<0.05) reported for pairwise differences detected by post-hoc tests. Logistic regression models were used to calculate the area under the receiver operator characteristic curve (AUROC) for discrimination between anaphylaxis and non-anaphylactic illness.ResultsHistamine concentration was significantly higher in the anaphylaxis group than the healthy (P < 0.001) and critically ill groups (P < 0.001), whereas no differences in MCT were detected amongst groups. Biomarker concentrations that were increased relative to healthy dogs in both the anaphylaxis and critically ill groups included IL-10 (P < 0.001 and P = 0.007, respectively), CCL2 (P = 0.007 and P < 0.001, respectively) and AST (both P < 0.001), whereas only the critically ill group had significantly increased CRP (P < 0.001), IL-6 (P < 0.001), KC (P < 0.001), ALP (P < 0.001), and fibrinogen (P = 0.016) concentrations, compared to the healthy group. Only dogs with anaphylaxis had significantly higher hyaluronan (P = 0.021) and ALT (P = 0.021) concentrations, and lower PC (P = 0.030) and AT (P = 0.032) activities, compared to healthy dogs. Both CRP and histamine concentration showed good discrimination between anaphylaxis and other critical illness, with an AUROC of 0.96 (95% CI 0.91–1) and 0.81 (95% CI 0.69–0.93), respectively.ConclusionsThis preliminary study in dogs with anaphylaxis after suspected insect exposure, found evidence of an early innate immune response, glycocalyx shedding and anticoagulant consumption. Both CRP and histamine showed potential clinical utility for differentiation between anaphylaxis and other critical illness.